2013
DOI: 10.1080/07399332.2012.736572
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing a Health Promoting Lifestyle in Spouses of Active Duty Military

Abstract: The purpose of this study was to understand the factors influencing the health promoting behaviors (HPBs) of military spouses. Pender's Health Promotion Model provided the theoretical framework guiding this study. One hundred twelve female spouses were surveyed regarding their perceived health status, perceived stress, self-efficacy, social support, and participation in HPBs. Perceived health status, self-efficacy, social support, and HPBs were positively related, whereas perceived stress was negatively relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The parents' role in undertaking infant care is very important because it affects the physical and mental conditions of the baby (Dokken and Ahmann, 2006;Day, Bernheimer and Weisner, 2007). The previous research shows that poor baby personality is associated with self-efficacy or parenting skills in infant care (Padden et al, 2013;Verhage et al, 2015).Therefore, it needs family support from other family members to optimally realize the parents' role (Hickey et al, 2016).Therefore, it needs powerful support from other family members in realizing the optimal parent role. Maternal Sensitivity Models (MSM) use family strength resources and family potential as key social support in enhancing the parental role so that MSM is proven to improve family perceptions on the parental role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parents' role in undertaking infant care is very important because it affects the physical and mental conditions of the baby (Dokken and Ahmann, 2006;Day, Bernheimer and Weisner, 2007). The previous research shows that poor baby personality is associated with self-efficacy or parenting skills in infant care (Padden et al, 2013;Verhage et al, 2015).Therefore, it needs family support from other family members to optimally realize the parents' role (Hickey et al, 2016).Therefore, it needs powerful support from other family members in realizing the optimal parent role. Maternal Sensitivity Models (MSM) use family strength resources and family potential as key social support in enhancing the parental role so that MSM is proven to improve family perceptions on the parental role.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal Sensitivity Models (MSM) interventions that make families as social support for other family members has formed a continuous interaction among family members in performing their roles, so that these conditions can effectively improve communication and harmony within the family. Social support of the family (physical, emotional and instrumental supports) in a parenting role has formed cognitive and affective awareness of the family members so as to perform their role (Padden et al, 2013;Pender, Murdaugh and Parsons, 2015). It is also in accordance with the results of the research conducted by Pontoppidan (2015) suggesting that family involvement programs in infant care are effective to overcome the physical and psychological problems of infants.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature on military spouse health shows research has primarily demonstrated negative effects of the military lifestyle on spouses’ mental health and the marital relationship, particularly during and after deployment [ 10 , 11 ]. In addition, a small number of studies have revealed concerning trends regarding obesity in military spouses, with estimates of overweight and obesity ranging from 47 to 65% [ 12 15 ]. However, military spouses’ perceptions of and participation in the health behaviors that likely contribute to these trends (i.e., physical activity and diet) have received minimal attention in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, military spouses’ perceptions of and participation in the health behaviors that likely contribute to these trends (i.e., physical activity and diet) have received minimal attention in the scientific literature. Two studies by Padden and colleagues demonstrated that high levels of perceived stress are associated with decreased participation in health behaviors such as exercise, stress management, and social interaction among military spouses [ 15 , 16 ]. Another study found only ~ 20% of military spouses reported engaging in regular physical activity and practicing good nutrition, and only 15% of the sample reported routinely practicing stress management [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Wives of military personnel show lower mental health due to their husband's difficult job, stress caused by husband's absence, heavy responsibility of family management, and instability of residence. [ 9 ] According to research, 34/1000 military pilots are at risk of mental health problems. [ 10 ] Common syndromes include anxiety (26%), marital conflicts (22%), somatization (15%), depression (13%), phobia (12%), and inappropriate behaviors (11%).…”
Section: Introductionmentioning
confidence: 99%